Comparing Prompting Strategies for Low-Resource Indonesian Languages: GPT-4o-mini and IndoBERT on Javanese and Sundanese - Fadilah, Sandi; Windiarti, Ika Safitri; Urva, Gellysa (Jurnal Teknologi Komputer dan Informasi, 2026)
Javanese and Sundanese are two of Indonesia’s most widely spoken regional languages, yet both suffer from severe underrepresentation in NLP research due to limited annotated data and few pre-trained resources. This study compares GPT-4o-mini and IndoBERT-base on three-class sentiment analysis for both languages using NusaX-Senti, evaluating zero-shot and few-shot prompting (nine examples) against an off-the-shelf fine-tuned classifier. Experiments used 100 stratified samples per language. GPT-4o-mini substantially outperforms IndoBERT-base: few-shot achieves Macro-F1 of 0.868 (Javanese) and 0.882 (Sundanese) versus 0.295 and 0.317 for IndoBERT (p<0.001, McNemar test). Few-shot prompting significantly improves Javanese performance (delta F1=+0.122, p=0.015), driven by the Neutral class (F1: 0.560 - 0.800), but shows no significant gain for Sundanese where zero-shot baseline already reaches 0.858. For Indonesian regional languages where domain-specific fine-tuning data is unavailable, prompted large language models offer a practical alternative to pre-trained BERT-based classifiers, requiring only minimal labeled examples rather than full retraining infrastructure.